A high-frequency EPR study of magnetic anisotropy and intermolecular interactions of Co(II) ions. (1st November 2021) - Spillecke, Lena; Tripathi, Shalini; Koo, Changhyun; Ansari, Mursaleem; Vaidya, Shefali; Rasamsetty, Amaleswari; Mallah, Talal; Rajaraman, Gopalan; Shanmugam, Maheswaran; Klingeler, Rüdiger
Graphical abstract: By employing detailed HF-EPR investigations on Co(II) ions we experimentally quantified the magnitude and the sign of the intermolecular interactions as well as the crystal field anisotropy parameters. Furthermore, a dependency of these parameters on the ions in the second coordination sphere has been ascertained. Abstract: Changing the anion in a crystal lattice induces distinct structural distortions in the [CoS4 ] 2+ core for a family of complexes with the general molecular formula [Co(L1 )4 ]X2, where L1 = thiourea (NH2 CSNH2 ) and X = I (1 ), Br (2 ), and [Co(L1 )4 ](SiF6 ) (3 ). The magnetic anisotropy (D) for 1 –3 was quantitatively determined with a magnitude of −153(2), −168(5) and < -400 GHz, respectively, by HF-EPR investigation. Also, intermolecular exchange interactions were determined experimentally, whereby an antiferromagnetic exchange for 1 (-5.5 GHz) and 2 (-4.1 GHz), and a ferromagnetic interaction for 3 (+3.5 GHz) are witnessed (based on H = -JS 1 S 2 ). The exchange interactions, computed using DFT methods on a model complex of 1, disclose the presence of an antiferromagnetic exchange interaction, consistent with the experimental observation. Overall, the present study provides convincing experimental evidence for the sizable influence not only of the first but also of the second coordination sphere on the magnetic anisotropy and exchange interactions of Co(II) ions.